Surveil and Let Surveil - Baranyi, Barnabás (Hungarian Journal of English and American Studies, 2020)
Book review: Flynn, Susan, and Antonia McKay, eds. Spaces of Surveillance: States and Selves. London: Palgrave, 2017. 278 pages. ISBN 9783319490847. Hb. 139.99.